Antagonistic Regulation of Parvalbumin Expression and Mitochondrial Calcium Handling Capacity in Renal Epithelial Cells - Henzi, Thomas (PLoS One, 2015)
Parvalbumin (PV) is a cytosolic Ca(2+)-binding protein acting as a slow-onset Ca(2+) buffer modulating the shape of Ca(2+) transients in fast-twitch muscles and a subpopulation of neurons. PV is also expressed in non-excitable cells including distal convoluted tubule (DCT) cells of the kidney, where it might act as an intracellular Ca(2+) shuttle facilitating transcellular Ca(2+) resorption. In excitable cells, upregulation of mitochondria in “PV-ergic” cells in PV-/- mice appears to be a general hallmark, evidenced in fast-twitch muscles and cerebellar Purkinje cells. Using Gene Chip Arrays and qRT-PCR, we identified differentially expressed genes in the DCT of PV-/- mice. With a focus on genes implicated in mitochondrial Ca(2+) transport and membrane potential, uncoupling protein 2 (Ucp2), mitocalcin (Efhd1), mitochondrial calcium uptake 1 (Micu1), mitochondrial calcium uniporter (Mcu), mitochondrial calcium uniporter regulator 1 (Mcur1), cytochrome c oxidase subunit 1 (COX1), and ATP synthase subunit β (Atp5b) were found to be up-upregulated. At the protein level, COX1 was increased by 31 ± 7%, while ATP-synthase subunit β was unchanged. This suggested that these mitochondria were better suited to uphold the electrochemical potential across the mitochondrial membrane, necessary for mitochondrial Ca(2+) uptake. Ectopic expression of PV in PV-negative Madin-Darby canine kidney (MDCK) cells decreased COX1 and concomitantly mitochondrial volume, while ATP synthase subunit β levels remained unaffected. Suppression of PV by shRNA in PV-expressing MDCK cells led subsequently to an increase in COX1 expression. The collapsing of the mitochondrial membrane potential by the uncoupler CCCP occurred at lower concentrations in PV-expressing MDCK cells than in control cells. In support, a reduction of the relative mitochondrial mass was observed in PV-expressing MDCK cells. Deregulation of the cytoplasmic Ca(2+) buffer PV in kidney cells was counterbalanced in vivo and in vitro by adjusting the relative mitochondrial volume and modifying the mitochondrial protein composition conceivably to increase their Ca(2+)-buffering/sequestration capacity.